2002
DOI: 10.1177/03635465020300020501
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Meniscal Allograft Transplantation

Abstract: Between May 1984 and December 1986, 23 patients with a history of medial meniscectomy and anterior knee instability were entered into a long-term prospective study of the results of medial meniscal transplantation combined with reconstruction of the anterior cruciate ligament. In 17 cases a lyophilized meniscal allograft was used and in 6 cases a deep-frozen meniscal allograft was used. The patients' clinical outcomes were evaluated 3 and 14 years postoperatively by clinical assessment, Lysholm score, radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
229
1
18

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(257 citation statements)
references
References 43 publications
9
229
1
18
Order By: Relevance
“…Our study showed that transplantation of medial and lateral meniscal allografts significantly reduces pain and improves function of the involved knee joint as measured with the modified HSS score. Our findings substantiate previously published reports on the clinical success of this procedure 4,7,[24][25][26] . Since the rate of clinical success of any surgical procedure is strongly dependent on the duration of follow-up, we performed a Kaplan-Meier survival analysis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed that transplantation of medial and lateral meniscal allografts significantly reduces pain and improves function of the involved knee joint as measured with the modified HSS score. Our findings substantiate previously published reports on the clinical success of this procedure 4,7,[24][25][26] . Since the rate of clinical success of any surgical procedure is strongly dependent on the duration of follow-up, we performed a Kaplan-Meier survival analysis.…”
Section: Discussionsupporting
confidence: 93%
“…This rating system has been used to determine knee function in previous reviews of the results of meniscal allografting procedures and of fresh osteochondral allograft procedures in combination with meniscal allografting 15,18,19 . Since meniscal allografting specifically relieves pain and improves function, the pain score and functional score of the modified HSS system were used for the evaluation of the clinical outcome and for the survival analysis [4][5][6][7] . The involved knee joint was evaluated by experienced examiners preoperatively and on a yearly basis postoperatively.…”
Section: Clinical Evaluation Of the Knee Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first 5 years after MAT, physicians can expect a mean Lysholm score of 80 points (range 60-100), with still values between 60 and 80 points at a follow-up between 10 and 20 years [7]. Also, several studies have reported a significant improvement in postoperative values of the Lysholm score compared to preoperative values [14][15][16][17][18][19]. Many studies found significant improvements after MAT in the International Knee Documentation Committee (IKDC) [11,14,15,17,18,20], with percentages between 70 to 90% of nearly normal or normal values [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical advantages of fresh-frozen over cryopreserved allografts are lower immunogenicity, easier process, and lower cost [48]. Lyophilized allografts are not currently recommended because of high percentage of graft shrinkage and greater likelihood of synovitis [19,38,53]. Nowadays, the most commonly used and recommended types of grafts are cryopreserved or fresh-frozen [6,7].…”
Section: Controversial Issues Graft Preservationmentioning
confidence: 99%